MODEL PERKULIAHAN BERDASARKAN KONSEP KINERJA PADA PEMBELAJARAN SEJARAH - Daliman, A. (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2015)
Abstract This application of history lecturing model based on performance concept was meant to raise the quality of the learning process and the students' achievement. To achieve that objective the lecturing model use the students oriented approach and multi-methods, consisting of: forum-lecturing, group task and work, discussion and seminar. The result of the research showed that the students' achievement were high in formative as well as summative evaluation. There was no student got grade of E (0%). Grade D were only 7.2%, grade of C was only 38.2 %, grade B was 38.2% and the grade A was 16.4%. Thus the percentages of the grades of B and A was >50%. Keywords: History lecturing model, performance evaluation, history learning